Training on the accountability management of special assistance funds in Batuah Village, Kutai Kartanegara Regency - La Ode Hasiara; Yulius Gessong Sampe Allo; Sailawati Sailawati (Universitas Muhammadiyah Magelang, 2022)
This program's goal is to educate 49 RTs in Batuah village, Kutai Kartanegara district, about how special assistance funds are managed and accounted for. Another objective is to give examples of evidence that can be accounted for so that the government, including the head of the RT and the village, is not entangled in the misappropriation of funds from the State or Region. With regard to the accountability management of special assistance funds for 49 RTs in Batuah village, Kutai Kartanegara district, the outcomes of the training activities were able to offer the participants significant benefits. It also stressed that regardless of assistance value, funds obtained from State or Regional finances must be used responsibly and supported by evidence that is both valid and trustworthy.